2018
DOI: 10.1002/jsde.12187
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sugar‐Based Gemini Surfactants and Their Surface Properties

Abstract: A group of novel sugar‐based gemini surfactants, N, N′‐bis(2‐hydroxy‐3‐alkyloxylpropyl) ‐N, N′‐bis(gluconylamide)‐ethylenediamine (alkyl: n‐C8H17, n‐C12H25, n‐C14H29, n‐C16H33), were synthesized and characterized. Their surface properties, including surface tension, γ, critical micelle concentration, CMC, maximum surface excess, Гmax, minimum area per molecule, Amin, and standard free energy of micellization and adsorption, normalΔGm0 and normalΔGads0, were investigated. The members of this family could reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Γ max values of both the surfactants decrease with the increase of the polymer concentration. A min , minimum area per the molecule at the air‐solution interface (Bhardwaj et al, ; Gan et al, ; Panda and Kamil, 2017), was calculated as (Eq. : Amin=1NA0.25emΓmax here, N A is Avogadro's number.…”
Section: Resultsmentioning
confidence: 99%
“…Γ max values of both the surfactants decrease with the increase of the polymer concentration. A min , minimum area per the molecule at the air‐solution interface (Bhardwaj et al, ; Gan et al, ; Panda and Kamil, 2017), was calculated as (Eq. : Amin=1NA0.25emΓmax here, N A is Avogadro's number.…”
Section: Resultsmentioning
confidence: 99%
“…In 2018, Gan et al reported the formation of vesicles and micelles from gemini surfactants based on glucono-δ-lactone, which depended on the length of the hydrocarbon chain as well as the surfactant concentration [92].…”
Section: Micelles Formationmentioning
confidence: 99%
“…SF-4-SF SF-6-SF 0.149 [27] 0.241 [27] [96] 0.049 [96] 0.042 [96] 0.033 [96] 0.0013 [97] 30 59.34 0.41 0.40 À 16.75 À 17.05 --PBBG 0.050 [55] 22 -------(PEG-MA-PEG) I II III IV 1.446 [98] 4.345 [98] 5.497 [98] 5.790 [98] (1-hydroxy-3,6,9,12,15,18,21,24,27,30,33,36,39-tridecaoxadotetracontan42yl)decanamide). benzene sulfonamide) with ethylene oxide was carried out at 150 °C.…”
Section: Scheme 31 Synthesis Of Zwitterionic Gemini Surfactants Nn-di...mentioning
confidence: 99%